17.1k views
2 votes
2(3x + 8) = -4(x + 6)
Can someone plz help

1 Answer

4 votes

Answer:

x= -4

Explanation:

1. First you distribute. Multiply 2 by both terms in the equation and multiply -4 by both terms in the equation. This gives you 6x+16 = -4x-24

2. Then, since the 4x is negative, you would add it to both sides to cancel it out. This gives you 10x+16 = -24 (4x was added to 6x making it 10x and it was added to -4x to cancel it out.

3. Then, since 16 is positive, subtract it from both sides to cancel it out. This gives you 10x = -40 (16 was subtracted from -24 making it -40 and from 16 to cancel it out).

4. Now divide 10 on both sides to cancel out the 10. You are left with x = -4

Hope this helps. I like to use Cymath, which gives a great step-by-step explanation.

User Akhilless
by
6.0k points